Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's carefully examine the given equation step-by-step:
### Step 1: Write Down the Equation
Given equation:
[tex]\[ (4x + 1)(3x - 7) - 2x(6x + 5) = 0 \][/tex]
### Step 2: Expand the Equation
First, we need to expand each term using the distributive property (i.e., multiplying through):
For \((4x + 1)(3x - 7)\):
[tex]\[ (4x + 1)(3x - 7) = 4x \cdot 3x + 4x \cdot (-7) + 1 \cdot 3x + 1 \cdot (-7) \][/tex]
[tex]\[ = 12x^2 - 28x + 3x - 7 \][/tex]
[tex]\[ = 12x^2 - 25x - 7 \][/tex]
For \(-2x(6x + 5)\):
[tex]\[ -2x(6x + 5) = -2x \cdot 6x - 2x \cdot 5 \][/tex]
[tex]\[ = -12x^2 - 10x \][/tex]
### Step 3: Combine and Simplify
Combine the expanded results:
[tex]\[ 12x^2 - 25x - 7 - 12x^2 - 10x = 0 \][/tex]
Combine like terms:
[tex]\[ 12x^2 - 12x^2 - 25x - 10x - 7 = 0 \][/tex]
[tex]\[ -35x - 7 = 0 \][/tex]
### Step 4: Determine Linearity
An equation is linear if its highest degree of the variable \(x\) is 1. Since the reduced form of our equation is:
[tex]\[ -35x - 7 = 0 \][/tex]
It is indeed linear because the highest degree of \(x\) in the equation is 1.
### Step 5: Solve for \(x\)
Solve the linear equation:
[tex]\[ -35x - 7 = 0 \][/tex]
Add 7 to both sides:
[tex]\[ -35x = 7 \][/tex]
Divide both sides by -35:
[tex]\[ x = \frac{7}{-35} \][/tex]
[tex]\[ x = -\frac{1}{5} \][/tex]
### Conclusion
The given equation is linear, and the solution for \(x\) is:
[tex]\[ x = -\frac{1}{5} \][/tex]
### Step 1: Write Down the Equation
Given equation:
[tex]\[ (4x + 1)(3x - 7) - 2x(6x + 5) = 0 \][/tex]
### Step 2: Expand the Equation
First, we need to expand each term using the distributive property (i.e., multiplying through):
For \((4x + 1)(3x - 7)\):
[tex]\[ (4x + 1)(3x - 7) = 4x \cdot 3x + 4x \cdot (-7) + 1 \cdot 3x + 1 \cdot (-7) \][/tex]
[tex]\[ = 12x^2 - 28x + 3x - 7 \][/tex]
[tex]\[ = 12x^2 - 25x - 7 \][/tex]
For \(-2x(6x + 5)\):
[tex]\[ -2x(6x + 5) = -2x \cdot 6x - 2x \cdot 5 \][/tex]
[tex]\[ = -12x^2 - 10x \][/tex]
### Step 3: Combine and Simplify
Combine the expanded results:
[tex]\[ 12x^2 - 25x - 7 - 12x^2 - 10x = 0 \][/tex]
Combine like terms:
[tex]\[ 12x^2 - 12x^2 - 25x - 10x - 7 = 0 \][/tex]
[tex]\[ -35x - 7 = 0 \][/tex]
### Step 4: Determine Linearity
An equation is linear if its highest degree of the variable \(x\) is 1. Since the reduced form of our equation is:
[tex]\[ -35x - 7 = 0 \][/tex]
It is indeed linear because the highest degree of \(x\) in the equation is 1.
### Step 5: Solve for \(x\)
Solve the linear equation:
[tex]\[ -35x - 7 = 0 \][/tex]
Add 7 to both sides:
[tex]\[ -35x = 7 \][/tex]
Divide both sides by -35:
[tex]\[ x = \frac{7}{-35} \][/tex]
[tex]\[ x = -\frac{1}{5} \][/tex]
### Conclusion
The given equation is linear, and the solution for \(x\) is:
[tex]\[ x = -\frac{1}{5} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.